An in vitro evaluation of biofilm removal from simulated root canals using sodium hypochlorite irrigation solution at various temperature settings - Kevser Şenel; Ismail Uzun; Rawan Alqawasmi (PLoS ONE, 2025)
Background Using sodium hypochlorite (NaOCl) irrigation solution at various temperatures is common for removing biofilms in root canals and the isthmus. Numerous studies have examined the impact of temperature on biofilm removal in extracted teeth. However, this study aimed to assess the effect of needle irrigation using NaOCl solution heated to different temperatures on the structure of E. faecalis biofilm in artificial teeth produced by 3D printing technology. Materials and methods The isthmus in the mesial canals of 55 artificial tooth samples, which were produced from the 3D model obtained by micro-CT of the mandibular first molars, was evaluated. The standard strain E. faecalis ATCC 19433 was used to infect artificial tooth specimens. The samples were divided into a control group and four experimental groups receiving sodium hypochlorite solutions at 21°C, 45°C, 60°C, and 150°C. Following irrigation, scanning electron microscope (SEM) imaging was conducted at varying magnifications to visualize the remaining biofilm areas in the root canals and the isthmus. The ImageJ program quantified biofilm areas in the isthmus region. Statistical analyses, including Shapiro-Wilks, Kruskal Wallis H, and t-tests, were conducted on the measurements. A p-value of < 0.05 was considered statistically significant. Conclusions The results did not differ between the control and 21 °C groups (p > 0.05). However, removal areas were larger in the 45°C, 60°C, and 150°C groups than in the control group (p < 0.05). No difference was observed in the biofilm removal efficiency in different isthmus regions (p > 0.05). The findings revealed that an increase in temperature enlarged the removal areas.